IMPLEMENTASI METODE UMMI DALAM MENGATASI KESULITAN MEMBACA DAN MENGHAFAL AL-QUR’AN DI RUMAH QUR’AN HIDAYATUL HAQ SINJAI - Suriyati; Nurqadriani; Jaya Nur, Makamur; Mustamir (LPPM STAI Muhammadiyah Probolinggo, 2024)
The study in the article can review how to implement the Ummi Method to avoid difficulties when reading and memorizing the Koran at the Hidayatul Haq Sinjai Qur'an House. The type of research used is qualitative research using a phenomenological approach and the data sources in this research are teachers (ustadz/ustazah), heads of Qur'an houses, students and other information related to this research. Collecting data was carried out by means of observation, interviews and documentation. In analyzing this data, researchers used qualitative data analysis techniques to process raw data from the field to increase understanding of the research object. Data Presentation: At this stage, carry out analysis by summarizing the data and drawing conclusions. The results of the research are data regardin.g how the Ummi method is implemented in the Qur'an house. They consider that this method is very effective because sentences or films that are continuously given repeatedly to students will indirectly be embedded in their brains until they understand. Apart from that, this method is also easy, fun and touching, meaning that children enjoy using this method.